Cross-border exchanges and volatility forecasting. Issue 5 (4th May 2018) - Goyal, Abhinav; Kallinterakis, Vasileios; Kambouroudis, Dimos; Laws, Jason
Abstract : We test for the performance of a series of volatility forecasting models (GARCH 1, 1; EGARCH 1, 1; CGARCH) in the context of several indices from the two oldest cross-border exchanges (Euronext; OMX). Our findings overall indicate that the EGARCH (1, 1) model outperforms the other two, both before and after the outbreak of the global financial crisis. Controlling for the presence of feedback traders, the accuracy of the EGARCH (1, 1) model is not affected, something further confirmed for both the pre and post crisis periods. Overall, ARCH effects can be found in the Euronext and OMX indices, with our results further indicating the presence of significant positive feedback trading in several of our tests.